Respuesta :
[tex]f(x)=2x^2+6x-4\\[/tex]
Find f(-5) by substituting x = -5 in the equation.
[tex]f(-5)=2(-5)^2+6(-5)-4\\f(-5)=2(25)-30-4\\f(-5)=50-34\\f(-5)=16[/tex]
Therefore, the answer is f(-5) = 16
Answer:
f(-5)=126
Step-by-step explanation:
what you would do first is plug -5 in for x which would give you the equation of f(-5)= 2(-5)^2 + 6(-5) -4
then you multiply the negative 5 and you will get
f(-5)= -10^2 + 30 -4
remove that square by multiplying -10 by -10 and you will get
f(-5)= 100 + 30 -4
combine like terms and you will get
f(-5)=126
i hope this helped you and that i explained it to you in a way that you understand